The Nigeria Hospitality Industry Experience on Customer Relationship Management and Marketing Effectiveness - Opara, Bright C. (Advances in Social Sciences Research Journal, 2016)
This study investigated the relationship between Customer Relationship Management (CRM) and Marketing Effectiveness (ME) in the Nigeria Hospitality industry. Structured questionnaire was employed as the instrument for data collection. The Cronbach’s Alpha Coefficient with a threshold of 0.7 was used to test the reliability of the research instrument, which showed CRM as a reliability coefficient of 0.763, while the Marketing Effectiveness is 0.838. The Spearman Rank order Correlation tool was employed to test the study hypotheses, in the SPSS package version 15. The major findings of this study showed that there is positive relationship between CRM and ME. The study also revealed that customer relationship management, and marketing effectiveness significantly impacted on Nigeria hospitality industry performance. Similarly, service automation significantly influenced ME in Nigeria hospitality industry. Since CRM, ME and service automation positively impact on industry performance; to achieve the desired ME in the Nigeria hospitality industry, marketing managers need to attract and retain customers through deliberate and consistent CRM policies and strategies. All staff therefore, should be given adequate marketing management orientation and training that would help to identify and treat customers as kings.